2004
DOI: 10.1182/blood-2003-11-3957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alpha hemoglobin stabilizing protein (AHSP) as a genetic modifier in patients with β thalassemia

Abstract: Although ␤ thalassemia is considered to be a classic monogenic disease, it is clear that there is considerable clinical variability between patients who inherit identical ␤ globin gene mutations, suggesting that there may be a variety of genetic determinants influencing different clinical phenotypes. It has been suggested that variations in the structure or amounts of a highly expressed red cell protein (alpha hemoglobin stabilizing protein [AHSP]), which can stabilize free ␣ globin chains in vitro, could infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 16 publications
1
89
0
1
Order By: Relevance
“…The relationships between AHSP and the thalassemia syndromes have been examined recently because these disorders involve HbA biosynthesis and a H and b H chain instability. Viprakasit et al (105) investigated whether variations in the apparent clinical severity of Hb E b thalassemia could be explained by the presence of mutant Ahsp alleles among affected individuals. Several single nucleotide polymorphisms (SNPs) were identified, but none of them were found to correlate with the severity of the thalassemic phenotype (105).…”
Section: Clinical Relevance Of Ahsp Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between AHSP and the thalassemia syndromes have been examined recently because these disorders involve HbA biosynthesis and a H and b H chain instability. Viprakasit et al (105) investigated whether variations in the apparent clinical severity of Hb E b thalassemia could be explained by the presence of mutant Ahsp alleles among affected individuals. Several single nucleotide polymorphisms (SNPs) were identified, but none of them were found to correlate with the severity of the thalassemic phenotype (105).…”
Section: Clinical Relevance Of Ahsp Functionmentioning
confidence: 99%
“…Viprakasit et al (105) investigated whether variations in the apparent clinical severity of Hb E b thalassemia could be explained by the presence of mutant Ahsp alleles among affected individuals. Several single nucleotide polymorphisms (SNPs) were identified, but none of them were found to correlate with the severity of the thalassemic phenotype (105). Other work has shown that both healthy and thalassemic individuals may possess an uncommon missense mutation that results in AHSP with an isoleucine at position 75 instead of an asparagine (N75I) (28).…”
Section: Clinical Relevance Of Ahsp Functionmentioning
confidence: 99%
“…Previously we reported that a certain AHSP haplotype has a lower level of expression and was related to a more severe phenotype of β-thalassemia (Lai et al, 2006). The allelic frequency of this AHSP haplotype was also found to be higher in a group of Hb E/ β-thalassemia patients compared to their non-thalassemic control group in Thailand by Viprakasit et al, 2004. However, when they analyzed this patient group with a non-thalassemic control group from another province, the AHSP allele frequency and haplotypes were more similar (Viprakasit et al, 2004).…”
mentioning
confidence: 96%
“…48,50 These studies in mice indicate that AHSP may be a possible modifier gene in human β-thalassemias. However, mutations which ablate AHSP in humans are rare 49,54 and investigations into possible effects of reduced AHSP expression in β-thalassemia have so far been largely inconclusive. Preliminary reports indicate that AHSP may be a modifier in the human population 48,[55][56][57] but as yet, there has been little definitive evidence that this is the case.…”
Section: Ahsp Functions In Vivomentioning
confidence: 99%